Political Ecology and the Historical Construction of Vulnerabilities in Indigenous-Rural Mexico: The Cholera Epidemic in Chiapas, 1991-1997 - Hernández Rivas, Marisol (Sekkan Revista de Ciencias Sociales y Humanidades, 2026)
This article analyzes, from a political ecology perspective, the historical processes that contributed to the construction of vulnerabilities in Chiapas and their relationship to the cholera epidemic that occurred at the end of the twentieth century. The argument is developed in three sections: the first presents key theoretical foundations of political ecology –such as the concepts of ecological debt, economic rationality, and environmental inequality– drawing on the critical approaches developed by Enrique Leff and Joan Martínez Alier, whose contributions help illustrate how power relations, development models, and the unequal distribution of resources intersect with the social production of vulnerabilities. The second section examines the interaction of specific processes that shaped structural vulnerabilities in Chiapas; and the final section explains the impact that these historically constructed vulnerabilities had during the cholera epidemic beginning in 1991. The research is based on a documentary and critical analysis of primary and secondary sources, including institutional historical archives, demographic and epidemiological data, contemporary press, community testimonies, and specialized literature. The findings show that limited access to drinking water and sanitation, precarious health services, and poverty were not circumstantial factors but expressions of a historically produced environmental injustice. The analysis demonstrates that territorial dispossession, institutional marginalization, and accumulated ecological debt contributed to greater exposure and reduced response capacity during the epidemic in Indigenous and rural communities. The main contribution of the study is to link the history of public health with long-term territorial processes, applying the principles of political ecology to a specific epidemic case. Among the limitations, the absence of direct fieldwork is acknowledged, suggesting that future research could broaden the approach through community-based and participatory methodologies.